Metabolic heterogeneity in the formation of low density lipoprotein from very low density lipoprotein in the rat: evidence for the independent production of a low density lipoprotein subfraction. - N H Fidge (Journal of Lipid Research, 1978)
The formation of low density lipoprotein (LDL) from very low density lipoprotein (VLDL) was studied after injecting 14C-radiomethylated or 125I-radioiodinated VLDL into rats. VLDL and LDL B apoprotein specific radioactivity time curves were obtained after tetramethylurea extraction of the lipoproteins. In all experiments, the specific activity of LDL B apoprotein did not intercept the VLDL curve at maximal heights, suggesting that not all LDL B apoprotein is derived from VLDL B apoprotein. Further subfractionation of LDL into the Sf 12-20, 5-12, and 0-5 ranges showed that most (65%) LDL B apoprotein was present in the Sf 0-5 fraction and that only a small proportion (6-15%) of this fraction was derived from VLDL. However, the curves obtained for the Sf 12-20 and 5-12 subfractions were consistent with a precursor-product relationship in which all of these fractions were derived entirely from VLDL catabolism. These results contrasted strikingly with similar data obtained for normal humans in which all LDL is derived from VLDL. In the rat, it appears that most of the B apoprotein in the Sf 0-5 range, which contains 65% of the total LDL B apoprotein, enters the plasma independently of VLDL secretion.